(Li6Si5)2–5: The Smallest Cluster‐Assembled Materials Based on Aromatic Si56− Rings. Issue 10 (25th January 2019) - Yañez, Osvaldo; Garcia, Victor; Garza, Jorge; Orellana, Walter; Vásquez‐Espinal, Alejandro; Tiznado, William
Abstract: Extensive explorations of their potential energy surfaces, combined with high‐level quantum chemical computations, strikingly show that the lowest energy structures of the (Li6 Si5 )2–5 systems consist of 2–5 Si5 6− aromatic units, surrounded by Li + counterions, respectively. These viable gas‐phase compounds are the pioneering reported cases of oligomers made by planar aromatic silicon rings. Based on the key evidence that these oligomers are energetically favored, and that their silicon rings aromaticity is thoroughly preserved, the Li6 Si5 cluster is proposed as a potential assembly unit to build silicon‐lithium nanostructures, thus opening new paths to design Zintl compounds at the nanoscale level. Abstract : Aromatic building blocks : After a systematic exploration of the potential energy surface of the (Li6 Si5 )2–5 clusters, it was found that the lowest energy structures in all cases are formed by multiple aromatic Si5 6− pentagonal units interacting electrostatically with lithium cations. These units maintain their geometric and electronic properties as revealed by chemical bonding and magnetic response analyses.